2014
DOI: 10.1063/1.4873587
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic energy harvesting using complementary split-ring resonators

Abstract: This work introduces a class of electrically small resonators composed of a complementary split-ring resonator backed by a ground plane. The proposed structure has low profile, efficient for wide range of illumination angles and can be placed on metallic surfaces. An example unit cell was designed, optimized, and fabricated to resonate at around 5.8 GHz. It is shown through numerical simulations and laboratory measurements that the complementary split-ring resonator can efficiently deliver the incident power c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…The DC power from the rectifiers is then combined in a power management circuit to obtain larger power. In [7], a ground-plane backed complementary split-ring resonator as an antenna for an energy harvester at 5.8 GHz was proposed. Although a rectifier has not been implemented yet, the aperture efficiency (the ratio of the effective aperture to the physical area of the resonator) is as high as 60 % by placing a ground plane closely behind the resonator.…”
Section: Introductionmentioning
confidence: 99%
“…The DC power from the rectifiers is then combined in a power management circuit to obtain larger power. In [7], a ground-plane backed complementary split-ring resonator as an antenna for an energy harvester at 5.8 GHz was proposed. Although a rectifier has not been implemented yet, the aperture efficiency (the ratio of the effective aperture to the physical area of the resonator) is as high as 60 % by placing a ground plane closely behind the resonator.…”
Section: Introductionmentioning
confidence: 99%
“…The open-ended surface currents distribution that was generated by various incident waves from the split-ring resonant lead to single-port collection with angle and polarization sensitive performance on a split-ring structure. So, the proposed square-ring MS structure can harvesting wide-angle, polarization-insensitive incident waves by optimizing the position of the harvesting point, and maintain high efficiency when compared to the structure described in the reference [6,[10][11][12] only collects single-polarized incident waves. By changing the value of each parameter of the MS structure (L, W, P, ε r , t), we can flexibly change the working frequency band, matching the load (R) value, to achieve the performance of effective energy harvesting.…”
Section: Design Of the Ms Energy Harvestermentioning
confidence: 99%
“…Different from the electromagnetic metamaterial absorber [4][5][6], the small split-ring resonators (SRR) were first used to collect energy in 2012 [7]. After that, some other SRRs [8][9][10], electric-inductive-capacitive (ELC) resonators [11], and ground-backed complementary split-ring (G-CSRR) resonator have also been proposed for electromagnetic energy harvesting [12,13]. The recently reported wideband ground-backed complementary split-ring (WG-CSRR) resonator structure can improve the bandwidth [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a conventional rectifying antenna array, the dimension of the element is generally comparable to a half free-space wavelength and the spacing between elements should be large enough to avoid the destructive mutual coupling between array elements. Some new types of electrically small energy collectors have been introduced, such as the ground-backed complementary split ring resonators (G-SRRs), 15,16 the wideband G-SRRs based on bow-tie cavities, 17 and the face-to-face split ring resonators. 18,19 It has been shown that, in contrast with a single resonator, an array of resonators with close proximity of each other can enhance the power harvesting efficiency.…”
Section: Introductionmentioning
confidence: 99%